2010
DOI: 10.1007/s11368-009-0172-z
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of perfluorinated compounds from contaminated water to activated carbon

Abstract: Introduction Perfluorinated compounds (PFC) are toxic and bioaccumulative compounds that are ubiquitous in the environment. It is important to develop effective techniques to remove PFC from water. This study is the first to investigate sorption of PFC to activated carbon (AC) at environmentally relevant nanogram per liter concentrations. Methods Batch AC sorption isotherms were measured for water from a contaminated groundwater well, for three perfluorosulfonates and five perfluoroacetic acids. Results For pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(71 citation statements)
references
References 14 publications
12
51
0
Order By: Relevance
“…In contrast, K F values for PFOA sorption from Zhi and Liu () and sorption of PFOS from Senevirathna, Tanaka, Fujii, Kunacheva, Harada, Shivakoti, Okamoto (2010) show a vast difference. There are little differences in Langmuir isotherm parameters reported in the literature and our study with the exception of Hansen, Borresen, Schlabach, and Cornelissen () which used contaminated well water with a very low initial concentration of PFAS and DOC.…”
Section: Resultsmentioning
confidence: 57%
“…In contrast, K F values for PFOA sorption from Zhi and Liu () and sorption of PFOS from Senevirathna, Tanaka, Fujii, Kunacheva, Harada, Shivakoti, Okamoto (2010) show a vast difference. There are little differences in Langmuir isotherm parameters reported in the literature and our study with the exception of Hansen, Borresen, Schlabach, and Cornelissen () which used contaminated well water with a very low initial concentration of PFAS and DOC.…”
Section: Resultsmentioning
confidence: 57%
“…PAC has a smaller size compared with GAC, and it has more micropores, surface functional groups and active adsorption sites, leading to the higher adsorption capacity (Yu et al, 2009b). Thus, PAC would adsorb PFASs faster than GAC due to its smaller particle size resulting in larger specific surface area for the same amount of carbon, extra surface functional groups, and shorter internal diffusion distances (Yu et al, 2009b;Hansen et al, 2010). Yu et al (2009b) found GAC and PAC were reached equilibrium at 168 h and 4 h for PFOA and PFOS, respectively.…”
Section: Removal Efficiencies and Mechanisms Of Pfass In Wwtps And Dwtpsmentioning
confidence: 99%
“…Yu et al (2009b) found GAC and PAC were reached equilibrium at 168 h and 4 h for PFOA and PFOS, respectively. An additional explanation of the poorer performance of GAC compared with PAC may be due to the rigidity of the CF 2 backbone which may render its sorption to the inner pore surface area of GAC energetically unfavorable (Hansen et al, 2010).…”
Section: Removal Efficiencies and Mechanisms Of Pfass In Wwtps And Dwtpsmentioning
confidence: 99%
“…Studies on fate and behavior of these pollutants in WWTPs implied that they could not be effectively removed by biological treatment process [5]. Various physical-chemical treatment processes, including adsorption [6][7][8], sonochemical treatment [9], reduction with zero-valent iron in subcritical water [10], and membrane filtration [11], have been employed to remove these compounds. Activated carbon adsorption is one of the most promising methods to remove PFCs in aqueous stream due to the effectiveness and low cost.…”
Section: Introductionmentioning
confidence: 99%